2008
DOI: 10.1021/ef800511v
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Polyphosphoric Acid and Bitumen Model Compounds with Oxygenated Functional Groups: Where Is the Phosphorylation?

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…It could be possibly from ketone groups. [26][27][28] There is no 13 C peak near 175 ppm which comes from a carboxyl (-COOH) group. [29][30][31] Since carboxyl groups have hydrogen, its 13 C peak must be cross-polarized if the groups are really present in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be possibly from ketone groups. [26][27][28] There is no 13 C peak near 175 ppm which comes from a carboxyl (-COOH) group. [29][30][31] Since carboxyl groups have hydrogen, its 13 C peak must be cross-polarized if the groups are really present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The broad peak at 195 ppm does not cross-polarize. It could be possibly from ketone groups [26][27][28]. There is no 13 C peak near 175 ppm which comes from carboxyl (-COOH) group [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…They all present, in the wavenumber interval scanned, three well-defined bands: the first, in the region 1760-1665 cm -1 due to the stretching vibration of the carbonyl (C=O) bond, and the second and third peaks, in the regions 1470-1350 and 1390-1370 cm -1 due to the bending vibration of the CH2&CH3 bonds and bending vibration of the CH3 bond, respectively [22]. However, only the "PG-H2SO4-150" sample displays a new absorption band, from 1060 to 1180 cm -1 , related to C−O−P vibrations [23]. Therefore, FTIR results provide evidences of the existence of chemical reactions involving phosphorus contained in the PG fraction which is not CaSO4 (about 8 wt.%), and which seem to be the responsible for the viscosity increase observed in Figure 1.…”
Section: Modification and Microstructurementioning
confidence: 99%
“…Using isolated model compounds containing oxygen functional groups (representative compounds for phenol, ether, ketone, and carboxylic acid), Masson et al concluded that phenols or aromatic carboxylic acids are not phosphorylated, indicating that phosphate esters cannot be responsible for the stiffening effect of PPA. 17 In two samples of PPA-modified bitumen derived from different sources of crude, Baumgardner et al observed a significant increase in asphaltene content (nheptane insolubles) with a reduced molecular weight, a decrease in resin content, and a nonmonotonous trend in the content of saturates; they proposed several possible underlying stiffening mechanisms such as the formation of PPA adducts, the alkylation of aromatics, and the formation of ionic clusters. 14 More or less, similar reports have documented the increase in asphaltene content and the decrease in resins/aromatics after PPA modification.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the mechanism underlying the specific interactions between PPA and SARA fractions that lead to the prominent features for PPA-modified bitumen is still elusive. Considering the inherent complexity of bitumen and the many unknowns in the interplay between PPA and a sea of bituminous molecular compounds, almost all we know about the molecular mechanism underlying the PPA interactions is limited to the studies performed on model compounds; data using 1 H NMR, 31 P NMR, and FTIR techniques is scarce. ,− On this basis, Giavarini et al and Orange et al suggested the phosphorylation of asphaltenes for increasing the amount of n -heptane precipitates. Using isolated model compounds containing oxygen functional groups (representative compounds for phenol, ether, ketone, and carboxylic acid), Masson et al concluded that phenols or aromatic carboxylic acids are not phosphorylated, indicating that phosphate esters cannot be responsible for the stiffening effect of PPA .…”
Section: Introductionmentioning
confidence: 99%